Cu(II)-enhanced activation of molecular oxygen using Fe(II): Factors affecting the yield of oxidants. (April 2019) - Chen, Yufan; Feng, Yong; Chu, Huaqiang; Wu, Deli; Zhang, Yalei
Abstract: Cu(II) enhanced the oxygen activation by Fe(II) to increase the yield of oxidants. However the factors controlling the catalytic performance and indeed the underlying influencing mechanisms remained unclear. Here, we presented the detailed study of Cu(II)-Fe(II) reactions for a range of pH and Cu(II)/Fe(II) ratios. From the results obtained, we provided insight into the factors controlling the redox reactions of Fe-Cu and the catalytic behaviours of active species. A reaction scheme for the Fe(II)/Cu(II) system was developed in which the in-situ formed Cu(I) mainly contributed to producing H2 O2 and Fe(II) dominantly decomposed H2 O2 to hydroxyl radical (HO ) [see companion article] (Yufan Chen). Circumneutral conditions facilitated the catalytic processes; under acidic conditions, the reverse reaction between Fe(III) and Cu(I) was strongly favoured; alkaline conditions improved the reducing capacity, which subsequently enhanced the generation of Cu(0) instead of Cu(I). There was a saturated Cu(II)/Fe(II) ratio above which further addition of Cu(II) could not be reduced, and then excessive Cu(I) and Cu(II) consumed HO and O2 –, respectively. Therefore, the highest removal efficiency of organic pollutants was achieved when the stoichiometric Cu(II)/Fe(II) ratio was 60% at circumneutral pH. The new findings have implications for the treatment of mixed wastewater where copper and organic pollutants coexist. Graphical abstract: Image 1 Highlights: Promoted yield of HO through the electron transfer mediated by Cu(II) from Fe(II) to O2 Generation of highly active Cu(I) facilitated by circumneutral conditions. In-situ formed Cu(I) predominantly contributing to the production of H2 O2 . Reactive oxygen species scavenged by excessive Cu(II).